Musa paradisiaca L. Inflorescence Abrogates Neutrophil Activation by Downregulating TLR4/NF-KB Signaling Pathway in LPS-Induced Acute Lung Injury Model - Francisco Allysson Assis Ferreira Gadelha; Raquel Fragoso Pereira Cavalcanti; Cosmo Isaias Duvirgens Vieira; Joao Batista De Oliveira; Louíse Mangueira De Lima; Adriano Francisco Alves; Matheus Marley Bezerra Pessoa; Leônia Maria Batista; Naiara Naiana Dejani; Marcia Regina Piuvezam (Pharmaceuticals)
Background/Objectives: Acute lung injury (ALI) is an inflammatory disorder affecting patients in intensive care with high mortality. No specific pharmacological treatment is available. Musa paradisiaca L. (banana) is a cosmopolitan plant, and homemade syrup from its inflorescence is used in many countries to treat pulmonary inflammation. Therefore, this study analyzed the hydroalcoholic extract (HEM) of the inflorescence on the ALI experimental model. Methods: Swiss mice were challenged with lipopolysaccharide and treated with HEM after 1, 24, and 48 h (five animals/group, three times). Results: The HEM-treated ALI mice presented a decrease in neutrophil migration in the bronchoalveolar lavage fluid (BALF), in the alveolar region, and in the blood, correlating to downregulation of CD18 expression. The HEM treatment also reduced the protein concentration in the BALF, caused lung edema formation, impaired NF-κB activation via inhibition of TLR4 signaling pathway, and decreased IL-1β, TNF-α production, free DNA release, and myeloperoxidase (MPO) activity. However, the extract induced an increased IL-10 in the BALF. Conclusions: Therefore, HEM’s anti-inflammatory and immunomodulatory activities in ALI mice are by deactivating neutrophils by decreasing CD18 receptor, free DNA release, and MPO activity and inducing IL-10 production. Thus, this study supports the use of banana inflorescence in folk medicine and suggests its rational use to develop a phytomedicine to treat pulmonary inflammation.